A highly selective and sensitive LC–MS/HRMS assay for quantifying coproporphyrins as organic anion-transporting peptide biomarkers. (December 2017) - Ramanathan, Ragu; King-Ahmad, Amanda J.; Holliman, Christopher L; Rodrigues, A David
Aim: Coproporphyrin-I (CP-I) and coproporphyrin-III (CP-III) in plasma and urine have been proposed as biomarkers for assessing drug–drug interactions involving hepatic drug transporters such as organic anion-transporting peptides (OATP), 1B1 and 1B3.Materials & methods: Plasma and urine extracts were analyzed for CP-I/CP-III using a TripleTOF API6600 mass spectrometer. Results: Previously unreported, CP-I/CP-III doubly charged ions ( m/z 328.14) were used as precursor ions to improve the assay sensitivity and selectivity over the singly charged precursor ions ( m/z 655.28). Levels of CP-I and CP-III measured ranged 0.45–1.1 and 0.050–0.50 ng/ml in plasma and 5–35 and 1–35 ng/ml in urine, respectively.Conclusion: The described highly selective and sensitive CP-I/CP-III LC–HRMS assay offers options for earlier characterization and clinical safety projections for OATP1B1/3-mediated drug–drug interactions along with pharmacokinetic analyses of a new chemical entity as part of first-in-human clinical studies.